How Parental Involvement Influences Adolescents' Academic Emotions from Control-Value Theory. - Dong, Yan; Wang, Hongfei; Zhu, Lin; Li, Chen; Fang, Yuan (Journal of Child & Family Studies, 2020)
Objectives: Parental involvement plays an important role in adolescents' cognitive, emotional, and social development. However, whether parental involvement will influence adolescents' academic emotions and, if so, what the underlining mechanism is have not been explored. This study aims to examine the mediation effects of adolescents' academic self-efficacy and academic value between parental involvement and academic emotions. Methods: In total, 391 triads (including students and their parents) participated in the study. Students ranged from 10 to 18 years old (M = 13.57, SD = 2.48) and included 194 males and 197 females. We established two models (both demonstrated acceptable model fit) to examine the mediation effects of academic value (academic intrinsic value and academic extrinsic value, respectively) and academic self-efficacy (academic self-efficacy of behavior and academic self-efficacy of ability, respectively). Results: Our results indicate that academic intrinsic value played a full mediating role between parental involvement and academic emotions (enjoyment and boredom). Academic self-efficacy of behavior exhibited full mediation between parental involvement and academic boredom, whereas academic self-efficacy of ability fully mediated the relationship between parental involvement and academic enjoyment. Conclusions: This study indicates that academic value and academic self-efficacy mediate parental involvement and academic emotions, broadening the research on parental involvement and supporting the control-value theory of academic emotions.